A Bibliometric Analysis of Generative Design, Algorithmic Design, and Parametric Design in Architecture - Brigitta Michelle; Maria Putri Gemilang (Journal of Artificial Intelligence in Architecture, 2022)
This research aims to display, compare, and analyze the keywords related to parametric design, generative design, and algorithmic design. Digital design has become increasingly inseparable from architects; thus, 3D modeling software has become a necessity for architects. The digital workflow has put computational design—generative design, algorithmic design, and parametric design—into importance. There are emerging trends for the past decade, and a bibliometric analysis can display information about trends in the literature. Literature trends may provide insight into the direction of computational design development. This study uses a bibliometric analysis with VOSviewer and data from Lens to identify the trends from 2011 to 2021. The result indicates several trends: artificial intelligence, computation, machine learning, visualization, and internet technology. The trend analysis needs to be continued in other computational design categories to find continuity in the findings.